Teaching for better thinking : the classroom communityof inquiry - Sharp, Ann Margaret; Splitter, Laurance (Hawthorn, Vic. : Australian Council for Educational Research, 1995)
THis book is about: The dynamics of the inquiring community; The making of meaning; Thinking philosophy and philosophy for children; The practice of philosophy in the classroom; Ethical inquiry in the classroom; ...
Keywords: Ethics; Philosophy; Thought and thinking; Philosophy -- Study and teaching (Primary); Ethics -- Study and teaching (Primary); Thought and thinking -- Study and teaching (Primary)